Efficacy and safety of Keluoxin capsule in combination with Western medicine for diabetic kidney disease: A systematic review and meta-analysis - Zhang, Wenhua; Zhou, Jingxin; Wang, Churan; Wang, Xu; Zhang, Shuwen; Jia, Weiyu; Jiang, Yijia; Lin, Lan; Gong, Yanbing (Frontiers in Pharmacology, 2023)
Objective: Keluoxin capsule (KLXC) has been widely used in diabetic kidney disease (DKD), but its efficacy and safety have not yet been clarified. A systematic review and meta-analysis were performed to assess the efficacy and safety of KLXC for DKD. Methods: The random control trials (RCTs) included KLXC were searched from 7 major English and Chinese databases up until June 3, 2022. The methodological quality and the risk of bias were assessed by version 2 of the Cochrane risk-of-bias tool (RoB 2) for RCTs from the Cochrane Handbook. The analyses were conducted by RevMan 5.4 and Stata 17.0. Results: A total of 20 trials with 1500 participants were identified. Meta-analysis showed that KLXC combined with western medicine was superior to western medicine alone for DKD including improvement in estimated glomerular filtration rate (eGFR) (MD = 3.04, 95% CI [0.30, 5.78], P = 0.03), reduction in microalbuminuria (mALB) (MD = -25.83, 95% CI [-41.20, -10.47], P = 0.001), urinary albumin excretion rate (UAER) (SMD = -0.97, 95% CI [-1.50, -0.44], P = 0.0003), 24-hour urine protein (24hUpro) (SMD = -1.31, 95% CI [-1.82, -0.80], P < 0.00001), serum creatinine (Scr) (MD = -11.39, 95% CI [-18.76, -4.02], P = 0.002), blood urea nitrogen (BUN) (MD = - 1.28, 95% CI [-1.67, -0.88], P < 0.00001), fasting blood glucose (FBG) (MD = -0.51, 95% CI [-0.90, -0.11], P = 0.01), total cholesterol (TC) (MD = -1.04, 95% CI [-1.40, -0.68], P < 0.00001), triglycerides (TG) (MD = -0.36, 95% CI [-0.50, -0.23], P < 0.00001), low-density lipoprotein cholesterol (LDL) (MD = -0.39, 95% CI [-0.71, -0.07], P = 0.02). Results showed no statistically significant difference in glycated hemoglobin (HbA1c) (P = 0.14) and adverse events (P = 0.81) between the two groups. Conclusion: The combination of KLXC and western medicine had a positive effect on DKD. However, due to the high clinical heterogeneity and low quality of included studies, further standardized, large-scale and rigorously designed RCTs for DKD in the definitive stage are still necessary to achieve more accurate results.